Environmental radiation assessment in the specified living areas for returnees of Okuma Town, Fukushima prefecture: Field measurements prior to decontamination - Kyoka Majima; Yuya Kashiwazaki; Hitomi Matsunaga; Makiko Orita; Noboru Takamura (PLoS ONE, 2026)
To assess environmental radiation exposure in the Specified Living Areas for Returnees of Okuma Town, Fukushima Prefecture, external radiation doses were evaluated using ambient dose equivalent rate measurements performed at residential properties. In addition to surveys covering the entirety of the Specified Living Areas for Returnees, area-specific assessments were conducted to account for differences in the progress of decontamination and demolition among districts. The median ambient dose rate measured by car-borne surveys across all Specified Living Areas for Returnees of Okuma Town decreased significantly from 0.49 µSv/h in November 2024 to 0.34 µSv/h in September 2025 (p < 0.05). In measurements conducted at residential properties prior to decontamination and demolition, the median ambient dose equivalent rate measured at house entrances was 0.96 µSv/h. The results of this study demonstrated that the ambient dose equivalent rates on roads measured by car-borne surveys across all Specified Living Areas for Returnees of Okuma Town decreased over the study period. In contrast, the estimated annual external dose at residential properties satisfied the reference level of 20 mSv set by the Ministry of the Environment as a guideline for lifting evacuation orders in most areas, but did not reach the long-term post-accident target level of 1 mSv. These findings provide evidence to inform ongoing discussions on evacuation order policies and long-term radiation management strategies.